2007
DOI: 10.1080/08989620701670161
|View full text |Cite
|
Sign up to set email alerts
|

EPA's 2006 Human-Subjects Rule for Pesticide Experiments

Abstract: Arguing that the 2006 Environmental Protection Agency (EPA) human-subjects rule allows use of unethical third-party research (on pregnant women and children) in setting pesticide regulations, this article first (a) provides a brief history of U.S. pesticide regulation, particularly regarding childhood safety. Next it (b) outlines ethical and scientific loopholes in the 2006 EPA rule; (c) shows how the Human Subjects Review Board, mandated by the 2006 rule, has been implemented in flawed ways; and (d) illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…For example, a pesticide company might conduct a study with a small sample size that shows no evidence of adverse effects of exposing human subjects to low doses of one of its products (Michaels, 2008; Shrader-Frechette, 2007). Because the study is underpowered, it is not likely to demonstrate a statistically significant adverse effect.…”
Section: How Financial Relationships Can Impact Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a pesticide company might conduct a study with a small sample size that shows no evidence of adverse effects of exposing human subjects to low doses of one of its products (Michaels, 2008; Shrader-Frechette, 2007). Because the study is underpowered, it is not likely to demonstrate a statistically significant adverse effect.…”
Section: How Financial Relationships Can Impact Researchmentioning
confidence: 99%
“…Researchers and institutions can have a significant stake in the outcome of a study if they own patents related to the research or they have stock in a company sponsoring the research. One reason why numerous authors have recently called for more studies of pharmaceuticals and industrial chemicals through government funding agencies such as the NIH and the National Science Foundation (NSF) is that these agencies are not seen as having a significant financial stake in obtaining specific outcomes (American Public Health Association, 2003; Volz and Elliott, 2012; Shrader-Frechette, 2007). Thus, while researchers funded by these agencies still face numerous pressures that can affect their judgment, financial stakes for the study sponsors are not perceived to be one of those influences.…”
Section: Taking Financial Relationships Into Account When Evaluating mentioning
confidence: 99%
See 1 more Smart Citation
“…Articles have examined financial COIs and sources of funding in research on the safety of industrial chemicals, 16,17 pesticides, 18 genetically modified foods, 19 sugar-sweetened beverages, 20 endocrine-disrupting compounds, 4,21 and electronic cigarettes. 22 Friedman and Friedman recently conducted a study of 373 articles published in 17 highly-cited environmental or occupational health journals in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey has revealed that fluoride inhibits sperm function, morphology, motility, induce sperm apoptosis and interrupt the sperm function, including capacitation, hyper activation and the acrosome reaction [4][5] all of which are the key process in fertilization, both in vivo and in vitro. Additionally, according to National Research Council annual report [6], fluoride is an endocrine disruptor altering normal endocrine functions thus might affect sperm function by binding to its receptors on spermatozoa.…”
Section: Introductionmentioning
confidence: 99%